3D printing for clothing production - Spahiu, Tatjana; Canaj, Eriseta; Shehi, Ermira (Journal of engineered fibers and fabrics, 2020)
3D printing is a well-known technology for creating 3D objects by laying down successive layers of various materials. Among the wide range of applications, fashion industry has adapted these technologies to revolutionize their brands. But due to the unique characteristics of textiles like comfort, flexibility, and so on, attempts have been made to create similar structures as textiles. The work presented here is part of a project to create garments using fused deposition modeling as 3D printing technology. Structures with various geometries are designed and tested with different materials starting from rigid to flexible. As a result, a fully 3D printed dress is created. Selecting this dress as a model, consumer acceptance for 3D printed garments is evaluated realizing an online survey containing 100 respondents. The data gathered show that respondents have knowledge of 3D printing, its advantages and the majority of them would accept wearing a 3D printed dress.